Application of Floyd‘s Algorithm on Transport Network of South Bohemian Region - Jiri Hanzl; Ladislav Bartuska; Elena Rozhanskaya; Petr Prusa (Communications - Scientific letters of the University of Zilina, 2016)
The introductory part of the paper deals with the theory of searching for optimal routes in transport networks, including a description of each type of optimization tasks. The aim of the article is demonstration of Floyd algorithm application to find the minimal paths from each node to another in network graph - in our case the network represents traffic model of road network in the region of South Bohemia.